Stability of mining pillars in stopes based on cusp catastrophe theory - WEN Xiaosong; WANG Chen; HUANG Xinxin; LONG Shaoliang; LI Cheng (矿业科学学报)
When exploitating deep-buried ore deposits, it is necessary to leave permanent pillars with certain width to ensure the stability of the mining area. Therefore, the reasonable design of pillar width is vital to its safety. Taking a phosphate mine in Guizhou as an example, this study derives an expression for the safety factor of pillars in mines using the filling method based on the Hoek-Brown strength criterion and pillar area load-bearing theory. Specifically, we analyzed the load-bearing mechanism of the pillars and established a square pillar instability model using the cusp catastrophe theory to obtain the necessary and sufficient conditions for the instability of square pillars. Results indicate that the width of the mine safety pillar should exceed 5.8 m in width, and the safety factor should not be less than 1.5. In the numerical simulation verification and actual production, the pillar width is set at 6 m. When the width of the pillar is designed to be 6 m, the maximum settlement displacement of the stope pillar is 14.75 mm, and the maximum stress is 3.88 MPa, which are within the stable and controllable range of the pillar. The numerical simulation results are basically consistent with the field monitoring results, and there is no obvious damage and cracking on the surface of the pillar. It shows that the cusp catastrophe theory is proved to be valid in explaining the mechanical mechanism of the instability of the pillar structure in mined-out areas, and its feasibility is validated in the stability analysis and parameter design of the pillars.